PREFERENSI KONSUMEN TERHADAP MEREK SMARTPHONE BERDASARKAN SISTEM OPERASI (Studi Perbandingan Smartphone menggunakan Iphone S/IOS dengan Android OS) - Putri Anggreni; I Wayan Gita Arsana (JUIMA : JURNAL ILMU MANAJEMEN, 2022)
This study aims to analyze the differences in smartphone brand preference in relation to android operating system and iOS, by analyzing the relationship between smartphone features and selection of smartphone brands based on android OS and iPhone OS, and the effect of the features offered Operating system used today by a brand smartphone with an interest in smartphone devices. Samples in this study as many as 100 respondents students in Denpasar City who use smartphones with iOS and Android operating system. By using convenience sampling method. Data analysis technique used in this research is multiple regression analysis and chi square test. The results of this study prove the difference in preference to smartphones with IOS and Android operating system, with Android smartphones have a greater preference than iOS smartphones. There is a connection between the smartphone feature and the preference to change the smartphone device it has.